Peningkatan Pemahaman Spldv Melalui Model Problem Based Learning (PBL) Pada Siswa Kelas IX - Wildamatuz Zahro; Arini Hidayati; Helmi Abdurrohim (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2026)
This study aims to improve students' understanding of the System of Linear Equations in Two Variables (SPLDV) through the application of the Problem-Based Learning (PBL) model to ninth-grade students. The low understanding of the SPLDV concept is caused by teacher-centered learning and the lack of active student involvement in the problem-solving process. This study used a Classroom Action Research (CAR) approach, implemented in two cycles, with each cycle encompassing planning, action, observation, and reflection. The subjects were ninth-grade students. Data collection techniques included conceptual understanding tests, observation of student activities, and documentation. The results showed an increase in students' understanding of the SPLDV material after the implementation of the PBL model. This was demonstrated by an increase in the average learning outcome score and student activeness in the learning process in each cycle. Thus, it can be concluded that the application of the Problem-Based Learning model is effective in improving students' understanding of the SPLDV material in ninth-grade students.